2013
DOI: 10.1016/j.jsams.2012.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Gene variants within the COL1A1 gene are associated with reduced anterior cruciate ligament injury in professional soccer players

Abstract: who were without any self-reported history of ligament or tendon injury. Both subjects and 6 healthy controls are from the same soccer teams, of the same ethnicity (Polish, East-Europeans for 7 ≥ 3 generations), a similar age category, and had a comparable level of exposure to ACL injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
2
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(126 citation statements)
references
References 29 publications
(38 reference statements)
9
101
2
5
Order By: Relevance
“…All these studies indicate that there is a strong (more than 50%) genetic influence on the nature if injuries occurring. Other studies show that the presences of these variations in DNA are related to injuries produced in the connective tissue although most of these studies have been performed in non-sports population [10][11][12][13].…”
Section: Genetic Variation and Detection Methodsmentioning
confidence: 99%
“…All these studies indicate that there is a strong (more than 50%) genetic influence on the nature if injuries occurring. Other studies show that the presences of these variations in DNA are related to injuries produced in the connective tissue although most of these studies have been performed in non-sports population [10][11][12][13].…”
Section: Genetic Variation and Detection Methodsmentioning
confidence: 99%
“…Since the previous ACL retreat, a growing number of common DNA sequence variants within genes involved in various biological processes have been associated with susceptibility to ACL rupture. These include variants within several genes that encode collagens [169][170][171][172][173][174][175] and proteoglycans 176 involved in the formation of the collagen fibril, the basic building block of ligaments. A subset of these variants has been specifically associated with ACL ruptures in females but not in males.…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…It was assumed that the predisposition for scars might be a polygenic trait; therefore, the haplotypes in two candidate polymorphisms would provide more information than those in any single polymorphism on the complex relationship between DNA sequence variations and traits. In fact, studies have shown that haplotype analysis is more powerful when the genotypes are in LD with the causative locus (19).…”
Section: Discussionmentioning
confidence: 99%
“…Ficek et al (19) reported that higher frequency of the GT haplotype was associated with reduced risk of ACL injury. Yazdanpanah et al (17) indicated a significantly high association of the GT haplotype with an increased risk of fragility fracture in women.…”
Section: Discussionmentioning
confidence: 99%